DIGITAL PH METER - Asmita Ashok Pakale; Pratibha Tanaji Jadhav; Pranali Dilip Jadhav (Journal of Electronic Design Engineering, 2018)
A pH Meter is an electronic device which is used for measuring the pH.The pH is either the concentration of Hydrogen ions in an aqueous solution or the active number of Hydrogen ions in an aqueous solution. The pH scale can measure that how acidic or basic a solution is. The pH scale has range of from 0 to14. A pH 7 of solution is neutral; A pH less than 7 of the solution is acidic. A pH greater than 7 of solution is basic. PH is defined as the negative logarithm of the hydrogen ion concentration.Using digital pH meter we get the numerical value of pH with more accuracy where as in conventional methods we get only indication that the solution is alkaline or base. As it gives the exact number of pH so it is easy to maintain the solution at neutral level. Also it gives the accuracy up to 0.01 %. In this work we used a magnetic stirrer or mixerwhich is employed for rotating the magnetic field for stirring the solution while sensing the hydrogen ionconcentration.